(untitled) (Translation: The University of Toledo Journal of Medical Sciences, 2025)
Lyme disease, caused by the spirochete Borrelia burgdorferi (Bb), is the most prevalent vector-borne disease in the United States. Macrophages, key cellular players in the innate immune response, exhibit diminished functionality over time during Bb infection, potentially leading to chronic infection. This study explores the transcriptional changes associated with macrophages that develop tolerance to Bb. Using RNA sequencing of murine bone marrow-derived macrophages exposed to Bb, we identified differentially expressed genes and dysregulated pathways between productively stimulated and tolerized macrophages. Key findings revealed significant downregulation of type-I interferon signaling and associated immune responses, suggesting mechanisms of immune tolerance. Additionally, connectivity analysis identified potential drug candidates for repurposing to enhance macrophage activity. Our results underscore the complexity of macrophage responses to Bb and provide a foundation for future research to develop targeted therapies aimed at modulating immune responses and improving treatment outcomes for Lyme disease patients. Ultimately, these findings offer new insights into the pathogenesis and potential treatment strategies for Lyme disease.